Short Communication: Exploratory AFLP-based genetic structuring among selected Selaginella species from Indonesia - AHMAD DWI SETYAWAN; TATIK CHIKMAWATI; MIFTAHUDIN MIFTAHUDIN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO; SUNARTO SUNARTO; YULITA KUSUMADEWI (Smujo International, 2025)
Abstract. Setyawan AD, Chikmawati T, Miftahudin, Sutarno, Sugiyarto, Sunarto. 2025. Short Communication: Exploratory AFLP-based genetic structuring among selected Selaginella species from Indonesia. Nusantara Bioscience 17 (2): 375-386. Selaginella is one of the oldest groups of living vascular plants and helps us understand how early land plants evolved and diversified. Despite its ecological and morphological diversity, molecular data remain limited for many tropical species. This study presents an exploratory assessment of multilocus genetic structuring among selected Selaginella species using Amplified Fragment Length Polymorphism (AFLP) markers. AFLP profiles were generated using four selective primer combinations, producing a total of 248 polymorphic fragments. Genetic similarity among species was quantified using Jaccard’s coefficient, and patterns of multilocus resemblance were examined through UPGMA clustering and principal coordinate analysis (PCoA). Pairwise similarity values ranged from 0.59 to 1.00, indicating a continuum of genetic differentiation rather than sharply delimited genetic groups. UPGMA clustering and PCoA revealed two broad species assemblages and substantial variation in multilocus genetic similarity among the analyzed taxa. The clustering pattern showed partial correspondence with major growth-form categories, with predominantly creeping to ascending species grouped separately from taxa exhibiting a cypress-like habit together with S. ornata. At the same time, several morphologically distinct species exhibited relatively high AFLP similarity, highlighting both congruence and incongruence between molecular and morphological patterns. Because the final comparative analyses were based on representative AFLP profiles for each species, the results should be regarded as an exploratory overview of interspecific multilocus differentiation rather than an assessment of intraspecific variation. Although AFLP markers do not permit direct phylogenetic inference, the findings provide a useful molecular baseline for future studies employing broader sampling and sequence-based or genomic approaches. Our findings demonstrate the value of integrating multilocus AFLP data with morphological evidence to better understand genetic structuring and species relationships in Selaginella. Although exploratory in nature, this study provides a useful molecular baseline for future sequence-based and genomic investigations.